In-hospital glycemic variability and all-cause mortality among patients hospitalized for acute heart failure - Kyeong-Hyeon Chun; Jaewon Oh; Chan Joo Lee; Jin Joo Park; Sang Eun Lee; Min-Seok Kim; Hyun-Jai Cho; Jin-Oh Choi; Hae-Young Lee; Kyung-Kuk Hwang; Kye Hun Kim; Byung-Su Yoo; et al. (Cardiovascular Diabetology, 2022)
Abstract Background High glycemic variability (GV) is a poor prognostic marker in cardiovascular diseases. We aimed to investigate the association of GV with all-cause mortality in patients with acute heart failure (HF). Methods The Korean Acute Heart Failure registry enrolled patients hospitalized for acute HF from 2011 to 2014. Blood glucose levels were measured at the time of admission, during hospitalization, and at discharge. We included those who had 3 or more blood glucose measurements in this study. Patients were divided into two groups based on the coefficient of variation (CoV) as an indicator of GV. Among survivors of the index hospitalization, we investigated all-cause mortality at 1 year after discharge. Results The study analyzed 2,617 patients (median age, 72 years; median left-ventricular ejection fraction, 36%; 53% male). During the median follow-up period of 11 months, 583 patients died. Kaplan–Meier curve analysis revealed that high GV (CoV > 21%) was associated with lower cumulative survival (log-rank P < 0.001). Multivariate Cox proportional analysis showed that high GV was associated with an increased risk of 1-year (HR 1.56, 95% CI 1.26–1.92) mortality. High GV significantly increased the risk of 1-year mortality in non-diabetic patients (HR 1.93, 95% CI 1.47–2.54) but not in diabetic patients (HR 1.19, 95% CI 0.86–1.65, P for interaction = 0.021). Conclusions High in-hospital GV before discharge was associated with all-cause mortality within 1 year, especially in non-diabetic patients with acute HF.